The dietary profile of socially vulnerable participants in health promotion programs in a brazilian metropolis - Raquel de Deus Mendonça; Paula Martins Horta; Luana Caroline dos Santos; Aline Cristine Souza Lopes (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
OBJECTIVES: To analyze the dietary profile of participants who used two health promotion services located in socially vulnerable areas in a Brazilian metropolis. METHODS: A cross-sectional comparative study was conducted with participants (n = 370) aged ≥ 20 years who joined two services of the Academias da Cidade program in Belo Horizonte, Minas Gerais, Brazil. The study participants engaged in physical activity and nutritional education actions directed by the services from 2009 to 2010. The sociodemographic and economic conditions and health and nutrition profiles of each individual were assessed. RESULTS: Participants from a high social-risk who used the service did not demonstrate adequate intake of vegetables (54.6 versus 43.6%; p = 0.038), sweets (33.5 versus 23.2%; p = 0.030), soft drinks (28.5 versus 11.9%; p < 0.001), artificial juice (34.7 versus 22.6%; p = 0.011), and processed meat (48.8 versus 32.7; p = 0.002). However, in the other service, lower social vulnerability, a higher prevalence of abdominal adiposity (60.7 versus 43.0%; p = 0.004) and consumption of high-fat meat products (53.0 versus 36.5%; p = 0.002) was observed. CONCLUSION: Participants who used both services demonstrated inadequate food intake compatible with the development of chronic disease profiles. However, the participants in each service were distinct from each other. This suggests that promotion of healthy eating should to contemplate the territory and its interface with people health.